Miscibility screening promotes the efficiency and stability of P3HT‐based organic solar cells - Kaihu Xian; Ruijie Ma; Kangkang Zhou; Junwei Liu; Mengyuan Gao; Wenchao Zhao; Miaomiao Li; Yanhou Geng; Long Ye (Aggregate, 2024)
Abstract The power conversion efficiency of organic photovoltaics (OPVs) has witnessed continuous breakthroughs in the past few years, mostly benefiting from the extensive use of a facile ternary blending strategy by blending the host polymer donor:small molecule acceptor mixture with a second small molecule acceptor. Nevertheless, this rather general strategy used in the well‐known PM6 systems fails in constructing high‐performance P3HT‐based ternary OPVs. As a result, the efficiencies of all resulting ternary blends based on a benchmark host P3HT:ZY‐4Cl and a second acceptor are no more than 8%. Employing the mutual miscibility of the binary blends as a guide to screen the second acceptor, here we were able to break the longstanding 10%‐efficiency barrier of ternary OPVs based on P3HT and dual nonfullerene acceptors. With this rational approach, we identified a multifunctional small molecule acceptor BTP‐2Br to simultaneously improve the photovoltaic performance in both P3HT and PM6‐based ternary OPVs. Attractively, the P3HT:ZY‐4Cl:BTP‐2Br ternary blend exhibited a record‐breaking efficiency of 11.41% for P3HT‐based OPVs. This is the first‐ever report that over 11% efficiency is achieved for P3HT‐based ternary OPVs. Importantly, the study helps the community to rely less on trial‐and‐error methods for constructing ternary solar cells.